2023
DOI: 10.1093/sleep/zsad029
|View full text |Cite
|
Sign up to set email alerts
|

Sleep of mothers, fathers, and infants: a longitudinal study from pregnancy through 12 months

Abstract: Study Objectives This study assessed and compared mothers’ and fathers’ sleep trajectories from pregnancy and throughout the first year of the infant’s life. We also examined associations between maternal, paternal, and infant sleep. Methods Two hundred and thirty-two couples were recruited for the study during pregnancy. Data were collected at pregnancy and at 4, 8, and 12 months postpartum. Maternal, paternal, and infant sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…First, maternal caregivers typically bear most of the responsibility for infant care, including feeding and nighttime care, particularly when breastfeeding is involved (Australian Institute of Family Studies, 2017). Consequently, maternal sleep is more closely linked to that of their infants than paternal sleep (Horwitz et al, 2023), and mothers of young children may experience greater disruptions in sleep patterns compared with fathers (Richter et al, 2019). Furthermore, when driving with an infant passenger, mothers may be more inclined to respond to infant signals such as crying, as they have lower tolerance for child distress than fathers (Kahn et al, 2018; Sadeh et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, maternal caregivers typically bear most of the responsibility for infant care, including feeding and nighttime care, particularly when breastfeeding is involved (Australian Institute of Family Studies, 2017). Consequently, maternal sleep is more closely linked to that of their infants than paternal sleep (Horwitz et al, 2023), and mothers of young children may experience greater disruptions in sleep patterns compared with fathers (Richter et al, 2019). Furthermore, when driving with an infant passenger, mothers may be more inclined to respond to infant signals such as crying, as they have lower tolerance for child distress than fathers (Kahn et al, 2018; Sadeh et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In line with previous studies (Armstrong et al, 2015; Maasalo et al, 2017; Sánchez‐García et al, 2019), we chose to focus the present investigation on women. This decision was made because mothers are typically more likely to be the primary caregiver for their infant, which may result in greater sleep disruption, and therefore an increased degree of vulnerability to impaired driving (Horwitz et al, 2023). We hypothesized that mothers of infants with insomnia would show poorer driving performance compared with both control groups, based on both self‐reports and objective driving assessment.…”
Section: Introductionmentioning
confidence: 99%
“…It should also be noted that EHR documentation of UTI signs and symptoms may not accurately represent patients' experiences. Studies using patient surveys 61–63 and audio or video recordings 64,65 of encounters have shown substantial discrepancies between patient‐reported and physician‐documented symptoms or examination findings. For example, a 2015 cross‐sectional study of hospitalized patients with Escherichia coli bacteriuria found low correlation between UTI symptoms as reported in patient surveys and documented in emergency physicians' ( κ = 0.09–0.5) and inpatient physicians' ( κ = 0.06–0.4) EHR notes 66 .…”
Section: Challenges and Limitationsmentioning
confidence: 99%
“…It should also be noted that EHR documentation of UTI signs and symptoms may not accurately represent patients' experiences. Studies using patient surveys [32][33][34] and audio or video recordings [35,36] of encounters have shown substantial discrepancies between patient-reported and physician-documented symptoms or exam findings. For example, a 2015 cross-sectional study of hospitalized patients with e. Coli bacteriuria found low correlation between UTI symptoms as reported in patient surveys and documented in emergency physicians' (κ,0.09-0.5) and inpatient physicians' (κ, 0.06-0.4) EHR notes.…”
Section: Challenges and Limitationsmentioning
confidence: 99%